Comparative Evaluation of Cross-table and Ducroquet Incidences for Measurement of the Hip Alpha Angle - Giancarlo Cavalli Polesello; Marcelo Cavalheiro Queiroz; Walter Ricioli Junior; Marco Rudelli; Marcus Aurelius Araújo Nunes; Denise Tokechi Amaral (Revista Brasileira de Ortopedia)
Abstract Objective The purpose of the present paper is to compare the equivalence of the measurement of the alpha angle using the Ducroquet and cross-table lateral views. Methods We have recruited 90 patients, resulting in 95 hips. We have standardized the realization of the radiographic views. The incidence of the lateral cross-table views were takenwith 15° of internal rotation with the patient in the supine position, and the incidence of the Ducroquet viewswas standardizedwith the patient in the supine position,with 90° of flexion and 45° of abduction of the hip. The alpha angle wasmeasured in both lateral views, by two musculoskeletal radiologists. The measurements were performed in 2 different times: an initial evaluation andanother 4weeks afterwards. The t Student test was usedand calculated the intraclass correlation coefficient (ICC). Results We have found a good intraobserver correlation for both views in different times; there was no statistically significant difference between the measurements performed by the two views. However, the interobserver correlation was low. Conclusion In conclusion, the Ducroquet profile view is a good choice for the α angle measurement and can be used instead of the cross-table view.